Transformasi Profesional Guru Pendidikan Anak Usia Dini di Era Society 5.0 - WIDIA ASTUTI; Muhammad Azhar Gunawan (Universitas Muhammadiyah Metro, 2026)
The advancement of technology in the Society 5.0 era positions Early Childhood Education (PAUD) teachers to develop digital literacy while maintaining humanistic pedagogical principles. This study employed a descriptive qualitative method to explore digital literacy, humanistic pedagogy practices, and technology integration among PAUD teachers in Yogyakarta. Data were collected through semi-structured interviews, participant observation, and document analysis, and were analyzed using data reduction, presentation, and triangulation verification. The results indicate variations in teachers’ digital literacy: 25% low, 41.7% moderate, and 33.3% high, affecting the integration of technology in learning. Teachers with low literacy tend to use digital media operationally, while those with high literacy support interactive and project-based learning. The analysis highlights the need for continuous digital literacy training balanced with humanistic pedagogy as a foundation for teacher competence development. contributes both practically and theoretically to enhancing the quality of safe, meaningful, and adaptive early childhood education in the Society 5.0 era.